1997
DOI: 10.1074/jbc.272.13.8346
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Uptake of Lead Is Activated by Depletion of Intracellular Calcium Stores

Abstract: The mechanisms of cellular lead uptake were characterized using a fluorescence method in cells loaded with indo-1. Pb 2؉ bound to intracellular indo-1 with much higher affinity than Ca 2؉ Lead is a ubiquitous environmental contaminant that can damage various organs, including those of the neurological, hematological, renal, and reproductive systems. Although it is readily taken up by many tissues, very little is known about the mechanisms of lead transport into cells. Lead is taken up in human red blood cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
74
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(79 citation statements)
references
References 32 publications
5
74
0
Order By: Relevance
“…This is in contrast to A23187 (Fig. 4B) (5,6,29) and because competition between these cations at intracellular sites is important in mechanisms of Pb 2ϩ toxicity (30,31). Using Equation 2 and the data in Fig.…”
Section: Ionophore-mediated Transport Of Pb 2ϩmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in contrast to A23187 (Fig. 4B) (5,6,29) and because competition between these cations at intracellular sites is important in mechanisms of Pb 2ϩ toxicity (30,31). Using Equation 2 and the data in Fig.…”
Section: Ionophore-mediated Transport Of Pb 2ϩmentioning
confidence: 99%
“…The identification of mechanisms leading to lead toxicity is therefore of considerable interest and actively investigated. Work of this type conducted at the cellular level has been facilitated by the recent demonstration that entrapped Indo-1 can be used to monitor Pb 2ϩ transport into cells (5,6), even though this fluorescent compound is responsive to changes in the intracellular free Ca 2ϩ concentration (7). Transport studies utilizing Indo-1-loaded cells of several types have shown that Pb 2ϩ enters via plasma membrane Ca 2ϩ channels that are activated upon depletion of internal Ca 2ϩ stores (5,6), as is also true for other toxic cations (8,9).…”
mentioning
confidence: 99%
“…Pb has an adverse effect on Fe deficiency, and Fe deficiency increases the absorption of Pb [17]. The absorption of Pb is positively correlated by the lower presence of Ca [18]. Fe is an important part of hemoglobin and myoglobin.…”
Section: Introductionmentioning
confidence: 99%
“…Hinkle (1997a, 1997b) also suggested that Pb 2+ is transported into cells via Ca 2+ channels. Experiments in cultured rat pituitary GH 3 cells, rat C 6 glioma cells, 301 cells (a subclone of Human Embryonic Kidney (HEK) 293 cells; Kerper and Hinkle, 1997a) and bovine brain capillary endothelial cells (Kerper and Hinkle, 1997b) indicate that Pb 2+ enters these cells via channels that are activated by the reduction of intracellular stores of Ca 2+ . These experiments also showed that the uptake of Pb 2+ was a time-and concentrationdependent process and was inhibited significantly by the addition of Ca 2+ .…”
Section: Leadmentioning
confidence: 99%